2021
DOI: 10.3390/ma14040849
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Tolerance and Charge Trapping Enhancement of ALD HfO2/Al2O3 Nanolaminated Dielectrics

Abstract: High-k dielectric stacks are regarded as a promising information storage media in the Charge Trapping Non-Volatile Memories, which are the most viable alternative to the standard floating gate memory technology. The implementation of high-k materials in real devices requires (among the other investigations) estimation of their radiation hardness. Here we report the effect of gamma radiation (60Co source, doses of 10 and 10 kGy) on dielectric properties, memory windows, leakage currents and retention characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In particular, the tunneling oxide will be more seriously damaged with more programming and erasing sequences, resulting in more charge leakage [ 15 ]. In order to overcome the issue of charge leakage, many device structures have been proposed, e.g., SONOS, BE-SONOS, TAHOS and 3D FLASH [ 6 , 17 , 18 , 19 , 20 ]. The 3D NAND FLASH structure was proposed as a solution when 2D NAND FLASH reached the scaling limit of a 15 nm process node [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the tunneling oxide will be more seriously damaged with more programming and erasing sequences, resulting in more charge leakage [ 15 ]. In order to overcome the issue of charge leakage, many device structures have been proposed, e.g., SONOS, BE-SONOS, TAHOS and 3D FLASH [ 6 , 17 , 18 , 19 , 20 ]. The 3D NAND FLASH structure was proposed as a solution when 2D NAND FLASH reached the scaling limit of a 15 nm process node [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Annealing in an oxygen ambient most strongly affects the charge storage ability of the stacks by increasing the number of trapped electrons and improving the stability of the stacks to a high electric field. Moreover, we have shown that Al 2 O 3 /HfO 2 stacks after RTA in O 2 are radiation-tolerant and their charge storage characteristics are not deteriorated by γ-irradiation [22].…”
Section: Introductionmentioning
confidence: 87%
“…The degradation of the memory window during the repeated write/erase operations is most likely due to wear-out mechanisms such as the generation of new bulk shallow traps and charges and interface state generation at the Si interface [46]. We have also investigated the radiation hardness of HfO2/Al2O3 CTL [47]. For this aim, the as-deposited and annealed 5×(30:10) stacks were subjected to 60 Co γ -irradiation with two radiation doses (10 and 100 kGy).…”
Section: Composition Of Charge Trapping Layermentioning
confidence: 99%
“…For this aim, the as-deposited and annealed 5×(30:10) stacks were subjected to 60 Co γ -irradiation with two radiation doses (10 and 100 kGy). During irradiation, no bias was applied to the We have also investigated the radiation hardness of HfO 2 /Al 2 O 3 CTL [47]. For this aim, the as-deposited and annealed 5×(30:10) stacks were subjected to 60 Co γ -irradiation with two radiation doses (10 and 100 kGy).…”
Section: Composition Of Charge Trapping Layermentioning
confidence: 99%
See 1 more Smart Citation